PRODUKSI SERASAH POHON Spathodea campanulata, Ficus benjamina DAN Palaquium obovatum DI TAMAN HUTAN RAYA GUNUNG TUMPA - Fahrudjia Umasugi; Wawan Nurmawan; Fabiola Saroisong (COCOS, 2022)
ABSTRACT Efforts to maintain the availability of nutrients on the soil are very important in efforts to maintain forest productivity. Litter are materials that have died, located above ground level that will later undergo decomposition and mineralization. The study aims to find out and compare the littering prodication of Spathodea campanulata, Palaquium obovatum, and Ficus benjamina trees in Mount Tumpa Forest Park. The study was conducted on the spathodea campanulata, palaquium obovatum, and ficus benjamina trees. The method of collecting the production of litters using litter traps placed under the trees Spathode campanulata, Palaquium obovatum, and Ficus benjamina is then taken once a week for three weeks. The results of this study showed that of the three main tree types on Mount Tumpa, the highest production with an average of 3,094.64 (g/tree) addressed by Ficus benjamina followed by Spathodea campanulata as many 1,119.99 (g/tree) and Palaquium obovatum as much as 600.71 (g/tree). Keywords : litter, production of litter, Mount Tumpa